TANGGUNG JAWAB PEMERINTAH DALAM PEMENUHAN PELAYANAN KESEHATAN TRADISIONAL SPESIFIK LOKAL: KOMPARASI INDONESIA DAN INDIA - Haryadi, Slamet; Novekawati, Novekawati; Riyanto, Slamet (Masalah-Masalah Hukum, 2024)
The Indonesian government needs to give more responsibility to traditional medicine. Because it can affect the quality and access to traditional health services. This study comparatively examines the responsibilities of the Indonesian and Indian governments to recommend improvements to the current Indonesian government policy regarding traditional health. This study is a normative legal study with a legislative approach sourced from primary and secondary materials. The results of the analysis show that the Indonesian government needs to learn from India's experience in strengthening the role of traditional medicine through support for research, education, and scientific development. The expected results of this study will be significant for the Indonesian government in making policies About Traditional Healthcare.